Investigation of metakaolin and steel fiber addition on some mechanical and durability properties of roller compacted concrete. (June 2022) - Abu-Bakr, Masood; Mahmood, Hersh F.; Mohammed, Azad A.
Abstract: In this experimental study, physical, strength and durability properties of roller compacted concrete (RCC) containing metakaolin with or without steel fiber are investigated. For this purpose, seven different mixes were designed and tested in the lab. To assess properties of compressive strength, splitting tensile strength, water permeability and freezing and thawing resistance in terms of weight and compressive strength losses. There is an increasing compressive strength of RCC containing MK with or without steel fiber with increasing ages. 15% MK 45 kg/m 3 steel fiber was found the best dosage for RCC at the age of 90 days. Also, there is a splitting tensile strength enhancement being increased with increasing MK and steel fiber in the mix. There is a continuous permeability reduction with increasing combined MK and steel fiber addition reaching 77.9% as maximum value for the mix of 20% metakaolin and 60 kg of steel fiber. Also, there is a reduction of weight and compressive strength losses of RCC subjected to freezing and thawing cycles up to 300 due to MK and steel fiber addition. It is concluded that using a combination of MK and steel fiber has a promised future to be used in more durable RCC for road construction.